2011
DOI: 10.1021/jp205104r
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effects and Interactions of Carbon Dioxide Molecules Adsorbed on Ni, Zn, and Cd Nitroprussides

Abstract: A thorough structural characterization of the synthesized Ni-, Zn-, and Cd-nitroprussides (NPs) with X-ray diffraction (XRD), thermogravimetric analysis, diffuse reflectance infrared Fourier transform spectrometry (DRIFTS), M€ ossbauer spectroscopy, and magnetic measurements was performed. However, the innovative part of the research was the study of the structural effects and the interactions of the CO 2 molecule with the Ni-, Zn-, Cd-NP frameworks. DRIFTS of adsorbed molecules, high pressure adsorption, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
0
15
1
Order By: Relevance
“…Thereafter, with the relation: q iso (0.37) = 1.16 E were calculated the isosteric heat of adsorption ( Table 5). The results reported indicated that the tested modified zeolites shows similar values for the measured isosteric heat of adsorption; but greater than those value of the isosteric heat of adsorption reported also in the present paper for the ZSM-5 zeolite, also larger than those reported for a particle packing silica and a dealuminated Y zeolite (DAY) [34], Cd, Zn and Ni-nitroprussides [41] and Cu-nitroprusside [40] and a Ni-MOF [39] (Table 6), as well bigger than experimental isosteric adsorption heats measured for the adsorption carbon dioxide on MCM-41- [58], silicalite [59], Na clinoptilolite and K-clinoptilolite [60], Na-A [61] and Na-X and MOF-5 [62] and MOF-508b [63], but similar to measured isosteric heats of adsorption for the adsorption of carbon dioxide on sodium ferrerite (Na-FER) [64]. The previously described adsorption data indicated that the interaction of the carbon dioxide molecule with the modified zeolites is strong.…”
Section: Resultscontrasting
confidence: 45%
See 3 more Smart Citations
“…Thereafter, with the relation: q iso (0.37) = 1.16 E were calculated the isosteric heat of adsorption ( Table 5). The results reported indicated that the tested modified zeolites shows similar values for the measured isosteric heat of adsorption; but greater than those value of the isosteric heat of adsorption reported also in the present paper for the ZSM-5 zeolite, also larger than those reported for a particle packing silica and a dealuminated Y zeolite (DAY) [34], Cd, Zn and Ni-nitroprussides [41] and Cu-nitroprusside [40] and a Ni-MOF [39] (Table 6), as well bigger than experimental isosteric adsorption heats measured for the adsorption carbon dioxide on MCM-41- [58], silicalite [59], Na clinoptilolite and K-clinoptilolite [60], Na-A [61] and Na-X and MOF-5 [62] and MOF-508b [63], but similar to measured isosteric heats of adsorption for the adsorption of carbon dioxide on sodium ferrerite (Na-FER) [64]. The previously described adsorption data indicated that the interaction of the carbon dioxide molecule with the modified zeolites is strong.…”
Section: Resultscontrasting
confidence: 45%
“…This detector is based on a Bruker AXS compound silicon strip technology and increases measured intensities, without sacrificing resolution and peak shape. This together with the use of small scanning step resulted in high quality XRD profiles suitable for mathematical treatment [39][40][41].…”
Section: Characterization Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The appearances of these two platinum species were as expected because of the use of Pt complex as a precursor. 38 The TGA prole of the Pt/Y/V and Pt/Y catalysts and the Na-Y zeolite are exhibited in Fig. 37 In Fig.…”
Section: Morphology and Structure Of The Catalystsmentioning
confidence: 99%